Establishment of a qualitative PCR assay for the detection of Xanthomonas albilineans (Ashby) Dowson in sugarcane. (April 2020) - Wang, Heng-bo; Xiao, Nai-yan; Wang, Yong-jun; Guo, Jin-long; Zhang, Ji-sen
Abstract: Xanthomonas albilineans (Ashby) Dowson ( Xa ) has devastating consequences on the vascular system of sugarcane plants and causes severe yield loss in sugarcane. In addition, the incubation period of the pathogen is long, and some infected varieties may remain symptomless for months and even years, leading to the spread of this pathogen over a large area. Therefore, it is important to establish a reliable and economical detection method for Xa . Based on the whole genome sequences of Xa, the hrpB gene was used to design 10 pairs of primers for the establishment of a novel qualitative PCR protocol. These pairs of primers were tested by species-specificity, annealing temperature, primer concentration and sensitivity. The most suitable hrp-10 primer pairs were chosen and used to detect the pathogen with assay sensitivity allowing the detection of 10 2 copies/μL of Xa purified DNA in suspension cultures. Moreover, sixty-eight sugarcane accessions (including 40 cultivars and 28 wild germplasms) with suspected infection by Xa from five provinces of China (Fujian, Yunnan, Hainan, Guangxi and Guangdong) were detected by the hrp-10 primer pairs. The results showed that the detection rate of the pathogen was 75% for symptomatic accessions, and 14% for asymptomatic samples. This newly developed PCR protocol provides a reliable and relatively inexpensive tool for the detection and identification of the pathogen Xa from infected sugarcane leaf. Highlights: Ten pairs of primers were designed by hrpB gene for establishment of a PCR protocol. The optimized hrp-10 primers can detect 10 2 copies/μL of X. albilineans. 75% (30/40) of symptomatic accessions were detected to be infected by X. albilineans. Abstract.